Redefining ’Community’: The Elusive Legacy of the Dramatists’ Co-op of Nova Scotia - Barton, Bruce (Theatre Research in Canada / Recherches théâtrales au Canada, 2000)
By many indications, playwriting in the Canadian Maritime provinces (Nova Scotia, New Brunswick, and Prince Edward Island) has never been more accomplished, diverse, and energetic. At the same time, however, many dramatists in this region experience a distinct and, for some, defining sense of isolation and disconnection from the rest of the country, particularly in terms of production opportunities beyond the East Coast. Aware of the limitations of local production, however enthusiastic the support of regional theatre companies and groups, a significant number of Maritimes playwrights lament the absence of vehicles—such as publication with national distribution—that may lead to increased profile for Maritimes drama within this country and internationally. At this juncture, it is particularly intriguing to consider the precedent of the Dramatists’ Co-op of Nova Scotia. A boisterous offspring of the Nova Scotia Writers Federation, the Co-op took upon itself the challenge to foster, promote, distribute, and generally champion Nova Scotian and, ultimately, Atlantic Canadian (including Newfoundland) drama for two decades following its inception in 1976. A fundamental difference between the dominant (although not exclusive) philosophy of Co-op members and their contemporary counterparts, however, is in the definition of the concept of ‘community.’ For, unlike the distinctly national and international interests regularly expressed in the current context, the Co-op placed a significant (although, again, not exclusive) emphasis on the establishment of a local community of theatre artists and, even more fundamental, of local theatre audiences. The contrast, while neither simple nor absolute, provides a productive point of entry into the complex reality of contemporary Maritimes dramatic practice. Plusieurs signes nous montrent que l’écriture théâtrale des provinces maritimes canadiennes (Nouvelle Ecosse, Nouveau Brunswick et l’Ile du Prince Edouard), n’a jamais été aussi accomplie, variée et vivante. Mais, en meme temps, beaucoup d’auteurs dramatiques de cette région se sentent separés, sinon isolés, du reste du pays concernant la production de leurs pièces audelà de la côte est. Conscients des restrictions d’une production limitée aux provinces maritimes, malgré l’aide enthousiaste des compagnies et des groupes régionnaux théâtraux, plusieurs auteurs dramatiques se lamentent du manque de publicité et de l’absence de diffusion nationale qui pourrait faire reconnaître leurs pièces dramatiques à l’échelle nationale et internationale. À ce moment, cela nous intrigue de penser au précédent de la "Dramatists’ Co-op of Nova Scotia." Progéniture tapageuse de la "Nova Scotia Writers Federation," la Coopérative a pris en charge le défi d’encourager, de promouvoir et de distribuer les pièces de Nouvelle Ecosse, aussi bien que celles de l’est du Canada (y compris Terre Neuve), pendant les vingt années qui suivirent sa conception en 1976. Mais il y a entre les membres de la Coopérative et ses contemporains une distinction philosophique dans la définition du concept ‘communauté’ qui va à l’encontre du terme dans les intérêts nationaux et internationaux. La Coopérative a donc insisté sur l’importance de la collectivité, de la localité de la communauté artistique, et encore plus, sur son public potentiel. Le contraste, ni simple ni absolu, permet un point d’insertion dans l’exercice compliqué du théâtre maritime canadien d’aujourd’hui.